Meningovertebral ligaments could be a barrier for migration of a herniated intervertebral disc: An anatomical study - Krystkiewicz, Kamil; Maślanka, Mateusz; Skadorwa, Tymon; Ciszek, Bogdan; Tosik, Marcin; Furtak, Jacek (Frontiers in Surgery, 2022)
Purpose: Intervertebral disc degeneration could manifest as a sequestration. In most cases, material could be found ipsilateral to the annular tear. However, sometimes contralateral migration is observed. We present anatomical description of the anterior meningovertebral ligaments as a possible barrier for the disc migration Methods: Anatomical dissection of 20 fresh human cadavers. Complete lumbar laminectomies and facetectomies were performed. All lumbar segments were exposed. Morphological and morphometrical description of the anterior meningovertebral ligaments was done, with the special attention to the possible routes of herniated disc migration. Results: Anterior meningovertebral ligaments were present in all cases. They were divided in 3 separate groups: medial, lateral and attached to the nerve roots. Medial ligaments were the thickest, mean length was 26,2±1,2 mm and had no attachment to the disc in 51% of cases. Lateral ligaments are less firm than medial, mean length was 26,9±1 mm and have no relation with the disc in 47% of cases. Ligaments related to the nerve root are most delicate and were always attached to the intervertebral disc. Their mean length was 14,95±1,8 mm. Conclusions: Medial meningovertebral ligaments are strong connective tissue bands dividing the anterior epidural space. Lateral group is more delicate and in most of cases, they lack an annular attachments. Meningovertebral ligaments could be the anatomical barrier for the disc migration in particular cases.